Evaluating intra row spacing to optimize techniques for artificial infestation of Striga hermonthica (Del.) Benth, screening for resistance in maize - Ibikunle, O.; Menkir, A.; Smith, M.; Kling, J. (2009)
A study was conducted to evaluate the use of different intra-row spacing to optimize Striga infesta- tion for resistance screening in maize. Five maize geno- types of different genetics backgrounds and contrasting reactions to Striga hermonthica were evaluated under four intra-row spacing. The experiments were conducted at Mokwa, and Abuja, in Nigeria for two and one season, respectively. Mean square for genotype × spacing interac- tion was not significant in the entire test environments. Thus, the same intra-row spacing can be used to effectively screen maize genotypes of difference genetic back- grounds while still obtaining optimum Striga infestation. Differences in intra-row spacing significantly affected Stri- ga emergence count, host plant damage symptoms and grain yield. On the average, the 20 cm intra-row spacing had over 100% Striga emergence than the 50 cm intra row spacing. However, the 20 cm intra-row spacing pro- duced the lowest grain yield under non-infested condition because of severe competition among maize plants within the row. The 25 cm spacing produced the highest Striga emergence and host plant damage symptoms as well as acceptable grain yield for all genotypes. The present arti- ficial field infestation techniques for Striga could therefore be further improved and optimized for better screening of maize germplasm for resistance if intra-row spacing be- tween 20 cm and 25 cm are adopted for effective separa- tion of reaction of maize genotypes to Striga.